INVESTIGATION OF THE CO₂ ABSORPTION COEFFICIENT IN AGGRESSIVE GAS ENVIRONMENTS - DUDATIEV, IHOR; MALTSEV, SERHII; PRYTULA, MAKSYM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This study investigates the absorption coefficient of CO₂ in the flue gas environment of boiler installations, focusing on the analysis of absorption spectra of combustion products to determine the optimal wavelengths for setting photodetectors in devices designed to monitor carbon dioxide concentration. The research includes an assessment of the average expected concentration of flue gases in boiler installations, which exceeds 0.1% by volume, within the infrared range of 0.75–15 µm (13330–667 cm⁻¹). The absorption spectra of key flue gas components, including CO₂, H₂O, N₂O, CO, and CH₄, are presented and analyzed in a unified coordinate system within the spectral range of 1–10 µm (1000–10000 cm⁻¹). Based on the obtained data, it has been established that the most intense absorption region lies within 2200–2500 cm⁻¹. A detailed graphical modeling of absorption in this spectral range was performed, allowing for an accurate determination of spectral band overlap characteristics and their influence on the absorption behavior of CO₂. Special attention is given to the spectral range of 4.1–4.3 µm (2300–2400 cm⁻¹), where a significant absorption band of CO₂ is observed. To improve the accuracy of CO₂ concentration monitoring in flue gases, a novel method for calculating the CO₂ absorption coefficient within this range is proposed. This method is based on the summation of Lorentz distributions for individual spectral lines, enabling a more precise evaluation of absorption intensity and providing a foundation for optimizing sensor calibration in industrial emission monitoring systems. Additionally, the study examines the influence of temperature and pressure variations on the absorption characteristics of CO₂ within the specified spectral range. A comparative analysis of experimental and theoretical absorption spectra is conducted to validate the accuracy of the proposed method. The findings highlight the importance of accounting for environmental factors in real-world applications and suggest potential improvements in sensor technology for continuous CO₂ monitoring in industrial and energy production facilities. This research contributes to the development of advanced gas analysis techniques and enhances the effectiveness of CO₂ detection in flue gas monitoring applications, ultimately supporting environmental and energy efficiency initiatives in industrial and boiler system operations.